Research in finance. Vol. 19 - Chen, Andrew H. (Emerald, 2002)
Since its first appearance in 1979, Research in Finance has been publishing papers that cover important and interesting issues in finance and economics. The topics found in the series span a wide range; previous volumes have included papers on corporate financial management policy, asset pricing and investment management, corporate control and governance, bank regulations and management, and the analysis of financial derivatives and their applications in risk management and in venture capital investment. These papers, among others, have made significant contributions to the literature. In this volume, Bajaj, Vijh and Westerfield present evidence showing that ownership structure affects a firm's agency costs of cash flow, which, in turn, influences the market's reaction to changes in the firm's dividend policy.McNabb and Martin examine the relationship between managerial entrenchment and the effectiveness of internal governance mechanisms and the firm performances.-In their paper, Kang, Karim and Rutledge apply a relative excess value ratio approach to empirically examine the association between the CEO compensations and the firms' performances. And Almisher, Buell and Kish, using accounting beta as a proxy for ex ante systematic risk of a firm, find a strong positive relationship between the firm's systematic risk and the subsequent degree of underpricing of its IPO. Also in this volume, Kwan and Wilcox show the disparity between accounting and actual cost reductions in bank mergers, and point out the importance of avoiding the accounting bias in reporting the cost reduction in bank mergers.Gunther and Siems empirically find that a desire to hedge balance sheet positions and having a strong capital position are the key motivations for banks' involvement in derivatives activities. Shyu and Reichert examine the key financial and regulatory factors that determine the derivatives activities of both U.S. and foreign banks.-In their paper, Yin, Wu and Chen explore the joint effects of the changes in capital regulation and deposit insurance system on banks' returns and risks in Taiwan. Based upon the one-factor equilibrium term structure model of Cox-Ingersoll-Ross, Chen and Chaudhury examine the market values and dynamic interest rate risks of existing swap positions.Chang and Ho derive formula of duration for different bonds under the Heath-Jarrow-Morton model of term structure and compare the relative performances of dynamic and static immunization strategies. In their paper, Boyle, Byoun and Park use intraday transactions data to show that the S&P 500 index option market leads the cash index, and that the lead-lag relation has resulted in a significant bias of the implied volatility that confirms their theoretical conjecture. Finally, Bubna uses a moral hazard model to address issues in the formation of syndicates in venture capital industry and to present some useful policy implications.-May the contributions within this volume be of significant interest and usefulness to its readers. And may Research in Finance continue to publish papers of the highest caliber, to the benefit of academics and practitioners alike.
Keywords: Finance -- Research.; Banks and banking.; elektronické knihy; electronic books